DIGITAL GAME BASED LEARNING UNTUK PEMBELAJARAN ARITMATIKA BAGI PENYANDANG TUNANETRA - Galang Prihadi Mahardhika; Husnul Anwar (Teknoin, 2018)
Visual impairment is a condition that causes one cannot access visual information clearly. Most of people with visual impairment access visual information through the sense of hearing and touch. One of activity which accessing visual information is indispensable is learning activities. Learning activities can affect one’s ability to understand and master what they learn. Moreover, in order to make learning activities more interesting, fun learning activities need to be created, such as learning while playing. The activities of learning while playing can be implemented by developing game based learning. This study was conducted to develop a game based learning that can help people with visual impairment to do learning activities for arithmetic subject. The interactivity in the game is a combination of touch and swipe interaction tehniques. From the user acceptance testing, result shows that the game is ease to use and to learn, and has a simple and intuitive interface. The next improvement for this game can be adding other interaction techniques such as hold, double click, multitouch, et cetera.